PEDAGOGICAL PROCESS MODEL OF DEVELOPMENT OF CHILDREN'S PHYSICAL CAPABILITIES IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Karimbaevna , Romanova Lola (PT. Antis International Publisher, 2024)
this article discusses the model of the pedagogical process of developing children's physical capabilities in preschool educational organizations